FORMULASI DAN UJI AKTIVITAS ANTIBAKTERI SEDIAAN LOTION EKSTRAK ETANOL DAUN DUKU (Lansium domesticum Corr.) TERHADAP BAKTERI Staphylococcus Aureus PADA PENYEMBUHAN PENYAKIT KULIT BERNANAH TAHUN 2022 - sulasmi sulasmi (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2022)
Duku leaves (Lansium domesticum Corr.) can be used as an alternative treatment for skin-related diseases such as boils caused by Stapylococcus aureus. Duku leaves contain flavonoids, saponins and triterpenoids that are able to provide antibacterial effects. This study aims to formulate duku leaf extract intopreparations lotion antibacterialagainst Stapylococcus aureus. The study was conducted experimentally, the sample was extracted by maceration method, then the extract was formulated intopreparations lotion with concentrations of 4%, 8% and 12%, of the three concentrations compared with positive control (caladin), negative control (basis lotion), then evaluation was carried out in the form organoleptic test, homogeneity test, dispersion test, pH test, irritation test and hedonic test for each formulation. After the evaluation data was obtained, an antibacterial test was carried out for each formulation. Then proceed with statistical analysis method One Way Anova. The results obtained at a concentration of 4% have the best formula in terms of organoleptic and hedonic (attractive color), thick shape, smells of perfume). In terms of pH it has a pH of 7.0; spreadability (6.27 cm ± 0.4); There is no irritation in this formulation. Based on statistical analysis, the sig Anova value of P < 0.05 (0.000) showed that there was a difference between each formulation in the concentration variation when compared to the positive control. Based on the antibacterial test the formulation concentration of 12% had the best antibacterial properties, namely 16.82 mm ± 4.00 compared to other formulations and the positive control had the best antibacterial properties, namely 17.32 mm ± 1.58. Based on statistical analysis, sig P value < 0.05 (0.000) which means that there are differences in each antibacterial formulation when compared with positive controls. The results showed that in terms of formulation, lotion with a concentration of 4% was the best formulation compared to other formulas. Based on antibacterial lotion concentration of 12% has the best antibacterial properties compared to other formulas.